Stimulating Six Aspects Of Development In Children Aged 4-5 Years Through Learning Assistance In Cihanjawar Village Rt 01 Bojong Purwakarta - Winarti, Wiwin; Adriansah (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The purpose of this devotion is to stimulate six developmental factors in children. Because the age range of 4-5 years is a golden age along the age range of human development. During this time the child is particularly receptive to stimuli from his environment. At that age, children also experience rapid growth and development both physically and mentally, so they need the right stimulus to optimize their growth and development. This service is carried out through learning assistance activities for children aged 4-5 years located in cihanjawar village Rt. 01. Because in cihanjawar village rt 01 there is no early childhood level school, the author conducts a program to stimulate six aspects of development in children through learning assistance, so that when entering the next level the child's development is optimal. It can be concluded that after the holding of learning assistance in early childhood in Cihanjawar village Rt.01, significant changes were seen in the development of each child. Seen in each activity, children show changes in their development through social interactions with adults and other children, where the child's interest and curiosity motivate him to learn while playing and there are individual variations in learning development.